A student guide to writing research reports, papers, theses and dissertations - Ó Siochrú, Cathal (London Routledge Taylor & Francis Group, 2023)
"This useful guide for students combines all the guidance, advice and key tips needed to write successful research reports, theses or dissertations, exploring, in detail, each of the elements involved in writing an academic paper. The book will guide you through all the key sections of a report including the introduction, literature review, method, results, discussion and more. Each chapter contains instructions and advice aimed at three different levels of report writing experience – ‘The basics’ covers the basic purpose and structure of each section as well as the most common mistakes, ‘Refinements’ helps you to develop your report writing skills beyond the basics, adding polish and depth, and ‘Advanced’ offers advice and insight into the most complex issues in report writing. In addition to the guidance, there are examples to show you the principles of report writing in action and exercises which allow you to test your understanding as you learn. An essential reference for any student writing an academic paper, A Student Guide to Writing Research Reports, Papers, Theses and Dissertations is the ideal resource to be used as part of your independent study or when working with a supervisor." -- Publisher's description.
Includes index.
Keywords: Dissertations, Academic -- Authorship; Academic writing